Bi-lateral CO2 emissions embodied in Australia–China trade. (May 2016) - Jayanthakumaran, Kankesu; Liu, Ying
Abstract: This paper quantifies the CO2 emissions embodied in bi-lateral trade between Australia and China using a sectoral input–output model. The results revealed: (1) that China performs lower than Australia in clean technology in the primary, manufacturing, energy sectors due to their overuse of coal and inefficient sectoral production processes, and (2) that China had a 30.94 Mt surplus of bi-lateral CO2 emissions in 2010–2011 and (3) overall global emissions were reduced by 20.19 Mt through Australia–China trade in 2010–2011. The result indicates that the greater the energy efficient a country among the trading partners the lower will be the overall global CO2 emissions. Global emissions decreased mainly because China consumed Australian primary products rather than producing them. Australia is an energy efficient producer of primary products relative to China. The bilateral trade compositions and trade volume played an important role in lowering global emissions and therefore one can view proposed China Australia Free trade Agreement positively in reducing global emissions. However, for the sustainable development, China should strengthen clean energy use and both countries should adopt measures to create an emission trading scheme in order to avoid protectionism in the form of future border price adjustments. Highlights: Primary (Australia) and manufactured (China) exports are a unique combination. Quantifies CO2 emissions embodied in bi-lateral trade between Australia and China. Global emissions reduce because China consume Australian primary. Australia is energy efficient producer of primary products relative to China. Results support more trade with appropriate trade composition and volume.